2015
DOI: 10.3399/bjgp15x683485
|View full text |Cite
|
Sign up to set email alerts
|

E-health and consultation rates for respiratory illnesses in infants: a randomised clinical trial in primary care

Abstract: BackgroundIt is assumed that clear and complete information on the internet can reduce healthcare consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Our findings in the young-age subgroup are in line with a recent study which found no change in healthcare usage for infants. 16 This suggests that the need for assurance by face-to-face contact cannot be replaced by eHealth in this patient group. The decrease in consultation rate was also present in the oldest subgroup.…”
Section: Discussion Key Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings in the young-age subgroup are in line with a recent study which found no change in healthcare usage for infants. 16 This suggests that the need for assurance by face-to-face contact cannot be replaced by eHealth in this patient group. The decrease in consultation rate was also present in the oldest subgroup.…”
Section: Discussion Key Results and Interpretationmentioning
confidence: 99%
“…Previous studies showed heterogeneous results: online information did not change or even increased healthcare usage in some studies. [8][9][10][11][12][13][14][15][16][17] An important limitation of these studies is that most estimated healthcare usage by patient self-reporting instead of actual healthcare usage statistics. Furthermore, the effects of online health information might be different in subgroups of sex, socioeconomic status Strengths and limitations of this study ▪ Long-term follow-up (6 years) in a large number of healthcare consultations (18.1 million).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could help them make better informed health decisions [14,18] and aid in improving communication between people and healthcare providers [1], as eHealth is often used to supplement physicians' recommendations [14,15]. Another advantage mentioned in the scientific literature is that eHealth allows people to access community support by facilitating participation in online support forums or in peer-support forums on social media [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…Parents also frequently use the internet to access health information for their children (Van Der Gugten et al, 2015). This trend is attributed to the decrease in the support of parents from close friends and family under post-modernism and the fact that the information they receive from their relatives is 'out of date'.…”
Section: Introductionmentioning
confidence: 99%